The degree of career polarization among educational leaders in the Jordanian Education Directorates - Mohammad Hasan Hamadat; Mohammad Omar Al-Momani (International Journal of Evaluation and Research in Education (IJERE), 2021)
The study aimed to identify the degree of career polarization among educational leaders in the Jordanian–education directorates of Ajloun and Jersah. The researchers adopted the descriptive -analytical approach for its suitability for such studies. The researchers used the questionnaire as the study instrument, which comprised 20 items. The researchers distributed the items in two domains, 10 items were for each domain as the study instrument. The sample of the study comprised 250 educational leaders for the first semester of the academic year 2019-2020. The study results showed that the degree of career polarization among educational leaders in the Jordanian Ministry of Education came with an average degree of rating in all its domains and for all items. The results also showed that there were no statistically significant differences at the level of statistical significance (α=0.05) attributed to the two study variables. Gender and the number of years of experience are the two study variables.